2018
DOI: 10.3390/atmos9050187
|View full text |Cite
|
Sign up to set email alerts
|

Projected Changes in Wet-Bulb Globe Temperature under Alternative Climate Scenarios

Abstract: Abstract:The increased levels of Greenhouse Gasses (GHGs) in the atmosphere will result in increased near-surface air temperature and absolute humidity. These two factors increasingly pose a risk of heat stress to humans. The Wet-Bulb Globe Temperature (WBGT) is a widely used and validated index for assessing the environmental heat stress. Using the output from the Coupled Model Intercomparison Project Phase 5 (CMIP5) simulations of the four Representative Concentration Pathways (RCPs), we calculated the globa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…W is defined as the temperature that an air parcel would reach through evaporative cooling once is fully saturated. As opposed to comfortbased heat indexes (Russo et al 2017;Matthews et al 2017;Li et al 2018) or more complex heat stress measures considering the effect of wind chill and solar irradiation (Dunne et al 2013;Newth and Gunasekera 2018), W establishes the clear thermodynamic threshold of 35 • C for which health impacts cannot be overcome by adaptation (Sherwood and Huber 2010). Exposure to instantaneous W values above 35 • C during periods as short as a few hours may be lethal even for acclimated healthy individuals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…W is defined as the temperature that an air parcel would reach through evaporative cooling once is fully saturated. As opposed to comfortbased heat indexes (Russo et al 2017;Matthews et al 2017;Li et al 2018) or more complex heat stress measures considering the effect of wind chill and solar irradiation (Dunne et al 2013;Newth and Gunasekera 2018), W establishes the clear thermodynamic threshold of 35 • C for which health impacts cannot be overcome by adaptation (Sherwood and Huber 2010). Exposure to instantaneous W values above 35 • C during periods as short as a few hours may be lethal even for acclimated healthy individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Most previous studies evaluating how these heat stress metrics change under global warming are based on smaller multi-model ensembles (Dunne et al 2013;Seneviratne et al 2016;Donat et al 2017;Mishra et al 2017;Matthews et al 2017;Russo et al 2017;Mora et al 2017;Newth and Gunasekera 2018;Coffel et al 2018;Li et al 2018;Bathiany et al 2018;Brouillet and Joussaume 2019), smaller regional model ensembles (Pal and Eltahir 2015;Im et al 2017), atmosphere-only ensembles (Lewis et al 2019), or smaller single-model ensembles (Sherwood and Huber 2010;Willett and Sherwood 2012;Mishra et al 2017). These smaller ensemble sizes imply a potential misrepresentation of the severity of future extremes in these studies.…”
Section: Introductionmentioning
confidence: 99%
“…8 Climate model simulations indicate that globally WBGT could increase from 0.6 to 4.4 • C by the end of the 21st Century, depending on the projected concentration of greenhouse gases. 24 Thus, using the 60th-90th percentile maximum WBGTs simulate the range of possible conditions. Most importantly, states in the responsive category will increasingly find themselves vulnerable and unprepared for climate change while those in the proactive category are better prepared (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…For future projections, CCSM4, MIROC5 and GISSE2-R were used (Hijmans et al 2005). I chose the RCP 8.5 because it has shown that distribution pattern of species corresponds to intensive scenario with rising temperature approximately to 2.37-4.4 ºC (Newth and Gunasekera 2018). All environmental layers have been extracted at a spatial resolution of 30 arc seconds (grid cells of ~ 0.0083° -approximately 1 km).…”
Section: Methodsmentioning
confidence: 99%